Analysis of performance indicators that most significantly affect International Twenty20 cricket. (4th May 2017) - Irvine, Scott; Kennedy, Rodney
Abstract: Twenty20 (T20) cricket has rapidly become the most lucrative and desirable format of the game, with performance analysis pivotal in shaping successful tactics and strategies. The purpose of this study was to determine the performance indicators that most significantly affect the outcome of a game of international T20 cricket, in different parts of the world. Cricket-specific analysis software was used to analyse 40 international matches from 2012 to 2016, across 7 different countries. Magnitude-based inferences determined that the total number of dot balls bowled (ES = 1.49), the total number of wickets taken (ES = 1.46) and the innings run rate (ES = 1.21) were the most significant indicators of success across the four environments. This indicates the need to select wicket-taking bowlers, for captains to gamble with attacking fields throughout the innings and for aggressive batters with a high strike rate and boundary % to be selected where possible. Furthermore, the main indicators of success remained constant across environments, with run-scoring and batting determinants greatest when in sub-continent conditions.